Glucose 6 phosphate dehydrogenase as a cause of neonatal jaundice - Say, Burhan; Berkel, Izzet; Çevik, Namık; Özand, Pınar (The Turkish Journal of Pediatrics, 1963)
A case of neonatal hyperbilirubinemia is reported. Tests indicated a glucose 6 phosphate dehydrogenase deficiency as the cause of the hemolytic disease. The authors have undertaken an intensive study of the incidence of G-6-PD deficiency in Turkey.